PENGARUH WORK-LIFE BALANCE TERHADAP KEBAHAGIAAN YANG DIMEDIASI OLEH SELF-ESTEEM PADA GURU SMK SWASTA DI KECAMATAN MAMPANG PRAPATAN - Isnaeni, Nurul; Parimita, Widya; Rahmadania, Rizki Firdaus (Indonesian Journal of Economy, Business, Entrepreneurship and Finance, 2023)
The purpose of this study was to examine the effect of Work Life Balance on Happiness mediated by Self Esteem of Private SMK Teachers in Mampang Prapatan District. Data collection in this study used an instrument in the form of an online questionnaire. Using random sampling technique. The sample used in this study were 76 respondents with the criteria of teachers who teach at private vocational schools in Mampang Prapatan District, South Jakarta. This research uses Smart PLS 3.2.9 with Outer Model and Inner Model analysis techniques. The results of this study indicate that Work Life Balance has a significant and positive effect on Self Esteem directly, Work Life Balance has a significant effect on Happiness directly, Self Esteem has a significant and positive effect on Happiness directly, and Work Life Balance has an indirect significant effect on Happiness with Self Esteem as a mediator